2015
DOI: 10.1186/s12955-015-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in caregivers of children and adolescents with Osteogenesis Imperfecta

Abstract: BackgroundOsteogenesis imperfecta (OI) is a group of genetic disorders of collagen biosynthesis, characterized by low bone density leading to fractures. Most patients exhibit functional impairment and require the aid of a caregiver. The aim of this study is to assess the quality of life (QoL) of caregivers of patients with OI.MethodsIn this cross-sectional study, a convenience sampling strategy was used to enroll adult caregivers of children and adolescents with OI who attended a referral center in southern Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 18 publications
5
46
2
1
Order By: Relevance
“…Majority of the caregivers in both groups were males (63.8% and 57.4%). This finding contrasts with similar studies that showed a majority of the caregivers of children with chronic diseases to be females [27] [28]. Furthermore, majority of the caregivers in both groups The overall QOL for respondents whose children do not have TB appears to be higher (mean 7.87 and SD 1.84) compared with respondents whose children have TB (mean 6.85 and SD 1.37).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Majority of the caregivers in both groups were males (63.8% and 57.4%). This finding contrasts with similar studies that showed a majority of the caregivers of children with chronic diseases to be females [27] [28]. Furthermore, majority of the caregivers in both groups The overall QOL for respondents whose children do not have TB appears to be higher (mean 7.87 and SD 1.84) compared with respondents whose children have TB (mean 6.85 and SD 1.37).…”
Section: Discussioncontrasting
confidence: 94%
“…These findings suggest that respondents whose children have TB have impaired QOL compared with those whose children do not have TB. This is consistent with the findings of several studies that measured the QOL of adult caregivers whose children suffered from chronic diseases such as osteogenesis imperfecta [27], sickle cell disease [31], cancer [32] [33], disabilities, Down's syndrome [34], speech and language disorders [35], COPD [28], and schizophrenia [36]. All these studies revealed that the caregivers of the diseased children had impaired QOL compared with control populations.…”
Section: Discussionsupporting
confidence: 90%
“…This issue contributed to stress and delay when seeking care for fractures. Caregivers (of children diagnosed with OI) QOL scores were lowest in the domains related to accessibility of social support and physical security for their children diagnosed with OI and family (Vanz et al., ). There is a need for a more family‐centered approach for developing resources for children diagnosed with OI and their families (Dogba et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast Vanz et al. () identified lower QOL scores for adolescents with OI and their parents in the psychological and environmental (financial resources, safety, opportunities to participate in recreation) domains.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation